Topoklimatska karta obalnega pasu Slovenske Istre - Ogrin, Darko (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2011)
The paper presents the basic topoclimatic features of the littoral zone in Slovenian Istria which result from general climate features and specific local conditions. The most widely spatially spread topoclimatic units arise from differences in insolation and the combination of local landforms and land use. They are presented on the map at a scale of 1 : 50,000.
Keywords: climatogeography; klimatogeografija; local climate; lokalno podnebje; obalna regija; Slovenia; Slovenian Istria; Slovenija; Slovenska Istra; topoclimatic mapping; topoklimatsko kartiranje